Dos átomos aos pixels: a reconfiguração do cartaz no contexto da cultura midiática - França, Andréa Ferreira de Andrade Poshar (2013)
The need of creating new means of communication guided by paradigm changes which comes out with the technological and technical development as well as by the manifestation of new cultures and economies in society, is more and more latent. Among these technological transformations, the poster would suffer some limitations consequences due to its printed graphics characteristics but as appropriated by the midiatic digitalization, this advertising gender presents nowadays some forms and interactive digital resources which were never seen before. Triggered by the midiatization processes and by digital culture, the instauration of technomediations established in the poster a new means of communication and relationship with an individual as well as with the environment in which he is inserted and so, fomenting a dynamic interaction of the digital resources available in this era. Nevertheless, wouldn´t it be normal that a means with such static and printed visual characteristics lose its functionality once it was reconfigured? While allowing the interaction and the link of devices to its support wouldn´t it be allowing it to be considered a poster? Such questionings are fundamental to this work which aims at trying to demonstrate the paradigm changes of the poster together with the technological innovations which have been going on till the digital culture in which it is inserted as a new social practice. We will also try to show the implications this new use of this means of communication is evoking in society: changes in collective environment, new relations of interaction of the individual with the digital, etc. So, we raise the hypothesis that despite the digital alterations the poster has suffered, it is still characterized and recognized as such, demonstrating the ability of adaptation and development it has along with the technologies of the time in which it is inserted.